ANALISIS DETERMINAN PENDAPATAN USAHA INDUSTRI MIKRO KECIL TAHU DI TRUNAN,TIDAR SELATAN,MAGELANG SELATAN KOTA MAGELANG - Khoirudin, Rifki; Setiaji, Wahyu Bagas (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2018)
This study aims to analyze the effect of venture capital, number of employees, work experience and working hours on the tofu micro industries income in Trunan, Tidar Selatan, South Magelang. This research data is obtained from questionnaire (primary) and several observations and interviews with related parties. The results showed that independent variables consisting of Venture capital, number of employees, work experience and working hours, together had an effect on the income of the tofu industries in Trunan with 5 percent significance level. Venture capital, number of employees, and business experience had a positive and significant effect on the tofu industries income in Trunan, while working hours had a negative and insignificant effect. With the R Square value of 95.8 percent, the effect of independent variables on the variable of the tofu industries income was 95.8 percent, while the remaining 4.2 percent was explained by other variables.